An adaptive End-to-End QoS Management for multimedia applications over wireless ATM network - F., Prihandoko; Mohd Ali, Borhanuddin; Habaebi, Mohamed Hadi; V., Prakash (IEEE, 2000)
The provision of multimedia application services over mobile wireless network is a very challenging problem. One major problem encountered is the maintenance of the QoS satisfaction for every application running over the network. Wireless ATM (WATM), as one of the next generation wireless system, is expected to provide such a service. After reviewing four current projects dealing with QoS management in the wireless network, this paper presents our approach to deliver an alternative solution to the problem, which is called AdQoS (Adaptive QoS). This system introduces some improvements over the other systems. The comparison among the techniques are presented and discussed.